Rational Design of a Hierarchical Tin Dendrite Electrode for Efficient Electrochemical Reduction of CO2. Issue 18 (27th July 2015) - Won, Da Hye; Choi, Chang Hyuck; Chung, Jaehoon; Chung, Min Wook; Kim, Eun‐Hee; Woo, Seong Ihl
Abstract Catalysis is a key technology for the synthesis of renewable fuels through electrochemical reduction of CO2. However, successful CO2 reduction still suffers from the lack of affordable catalyst design and understanding the factors governing catalysis. Herein, we demonstrate that the CO2 conversion selectivity on Sn (or SnOx/Sn) electrodes is correlated to the native oxygen content at the subsurface. Electrochemical analyses show that the reduced Sn electrode with abundant oxygen species effectively stabilizes a CO2.− intermediate rather than the clean Sn surface, and consequently results in enhanced formate production in the CO2 reduction. Based on this design strategy, a hierarchical Sn dendrite electrode with high oxygen content, consisting of a multi‐branched conifer‐like structure with an enlarged surface area, was synthesized. The electrode exhibits a superior formate production rate (228.6 μmol h−1 cm−2) at −1.36 VRHE without any considerable catalytic degradation over 18 h of operation.